Malaria and Chinese economic activities in Africa - Matteo Cervellati; Elena Esposito; Uwe Sunde; Song Yuan (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We present novel evidence for the influence of malaria exposure on the geographic location of Chinese economic activities in Africa. The hypothesis is based on the observation that many Chinese aid projects and infrastructure contractors rely on Chinese personnel. High malaria exposure might constitute an important impediment to their employment and productivity. Combining data on Chinese aid and construction projects with geo-localized information about the presence of individuals from internet posts reveals a lower density of Chinese activities and of Chinese workers in areas with a high malaria exposure. This effect is mitigated partly through heterogeneity across sectors and immunity of the local population, through the selection of Chinese workers from regions in China with historically high malaria risk, and through the availability of malaria treatment.
Keywords: F2; F6; J2; J6; 330; Infrastructure Projects; Malaria; Disease Prevalence; Immunity; Weibo